5=6x-5(-2x-17)

Simple and best practice solution for 5=6x-5(-2x-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=6x-5(-2x-17) equation:


Simplifying
5 = 6x + -5(-2x + -17)

Reorder the terms:
5 = 6x + -5(-17 + -2x)
5 = 6x + (-17 * -5 + -2x * -5)
5 = 6x + (85 + 10x)

Reorder the terms:
5 = 85 + 6x + 10x

Combine like terms: 6x + 10x = 16x
5 = 85 + 16x

Solving
5 = 85 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
5 + -16x = 85 + 16x + -16x

Combine like terms: 16x + -16x = 0
5 + -16x = 85 + 0
5 + -16x = 85

Add '-5' to each side of the equation.
5 + -5 + -16x = 85 + -5

Combine like terms: 5 + -5 = 0
0 + -16x = 85 + -5
-16x = 85 + -5

Combine like terms: 85 + -5 = 80
-16x = 80

Divide each side by '-16'.
x = -5

Simplifying
x = -5

See similar equations:

| -5(6-x)+5=3(x-2) | | 9-5x+3=3x+4 | | -5(x-3)=-24 | | 3(2c+8)=72 | | 5+25-1=7s+9-45 | | 0.17y+0.07(y+4000)=1960 | | x/x-2=6/7 | | 9x-5x+3=3x+4 | | 13p+9=13+6p | | 10x+3=3x+52 | | 3r+2r=-35 | | 6(x-5)-2(2x+4)=3(x-10) | | x/(x-2)=6/7 | | 2/3(2/3m-2/3) | | 14-28= | | -61(z-56)=z+(-28) | | -3(2y-4)-y=-4(y-4) | | (2/3)(m-30)=(2/3)m+10 | | 4/3x-3=x+2/3-1/3x | | 7x-6-4x=12+3x-8 | | -33+63= | | 83/14-7r=3/2(-10/3r+9/7) | | 3(9x-17)=0 | | (-7/4)-(1/2x) | | 6+-21= | | 4x-14=2x+6 | | (8x+3)*(6x^2+7x+9)=0 | | 109/24+3.3/4x=1/4+1/3(x-5/2) | | x^2-121=o | | 2(4z-1)=3(z-2) | | 15=-6n-7+2n | | q=4p+1 |

Equations solver categories